2013
DOI: 10.1097/jfn.0b013e31829beb1e
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Alternative Light Source to Assess Strangulation Victims

Abstract: Alternative light sources (ALSs) are commonly used at crime scenes and in forensic laboratories to collect evidence such as latent fingerprints, body fluids, hair, and fibers. This article describes the use of this technology to reveal soft tissue injuries that are not visible to the naked or unaided eye in patients who report strangulation. The value of this information to the medical, nursing, and judicial systems is discussed. The records of the 172 strangulation patients seen in our forensic nurse examiner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 1 publication
0
52
0
Order By: Relevance
“…Gross observation of light absorption by these molecules requires the use of alternate light, specific wavelengths which may include the visible (400-700 nm) or long ultraviolet (290-400 nm) spectrums (19). Generally, light is reflected, transmitted, scattered, and/or absorbed by the skin's surface (20,21) Transmitted light can be absorbed and reflected by deeper structures, with longer wavelengths generally having greater skin penetration (20). Filters (e.g., colored goggles and camera lenses) can then be used to block the reflected light allowing the absorbed light to appear darker by comparison (19).…”
Section: Abstract: Alternate Light Bruises Detection Injury Ultramentioning
confidence: 99%
See 2 more Smart Citations
“…Gross observation of light absorption by these molecules requires the use of alternate light, specific wavelengths which may include the visible (400-700 nm) or long ultraviolet (290-400 nm) spectrums (19). Generally, light is reflected, transmitted, scattered, and/or absorbed by the skin's surface (20,21) Transmitted light can be absorbed and reflected by deeper structures, with longer wavelengths generally having greater skin penetration (20). Filters (e.g., colored goggles and camera lenses) can then be used to block the reflected light allowing the absorbed light to appear darker by comparison (19).…”
Section: Abstract: Alternate Light Bruises Detection Injury Ultramentioning
confidence: 99%
“…An alternate light source (ALS) has been suggested by the U.S. Department of Justice as a tool to assist in identifying evidence of "subtle injury" (22). However, prior research on whether an ALS is effective at clinically detecting bruising within the visible and ultraviolet spectrums is limited (21,(23)(24)(25). The few available studies have found use of an ALS enhanced bruise observation, but researchers were unable to control for the potential effects of false positives either through study design (21,24,25) or execution (23).…”
Section: Abstract: Alternate Light Bruises Detection Injury Ultramentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that 93% of the victims had no visible evidence of external injuries upon examination without the ALS. Once the ALS was used, intradermal injuries were found in 98% of those patients (Holbrook & Jackson, 2013).…”
Section: Physical Findingsmentioning
confidence: 99%
“…Alternate light and its ability to aid in visualization of sub-dermal bruises, visible and invisible to the naked eye has been examined in a small number of previous studies (Holbrook & Jackson, 2013;Limmen et al, 2013;Lombardi, Canter, Patrick, & Altman, 2015). None of these examined whether commonly used topical products absorb under various wavelengths of light.…”
Section: Introductionmentioning
confidence: 99%